Zasada racji dostatecznej w kontekście semantycznej kontrowersji realizm–antyrealizm - Jarosław, Boruszewski (My University, 2013)
"Principle of sufficient reason in the context of the realism-antirealism semantic controversy". The topic of this article is the cognitive and semantic status of Michael Dummett’s principle C. According to the principle, if a statement is true, there must be something in virtue of which it is true. The author suggests the interpretation of principle C in terms of the sufficient reason principle as a contemporary, weaker and semantic counterpart of the classical version of the principle. Considerations include such problems as: the distinction between the reason-consequence relationship and cause-effect relationship; the reductionism and justificationism in the context of the realism-antirealism semantic controversy; the reversibility of reason-consequence relationship and the question of a search for ultimate reasons. The author also distinguishes three forms of the sufficient reason principle: metaphysical, ontological and propositional.
Keywords: Donald Davidson; Michael Dummett; antyrealizm semantyczny; zasada racji dostatecznej; justyfikacjonizm; stosunek racji i następstwa; trylemat Friesa; Trylemat Münschausena; krytyczny racjonalizm